(untitled) (Моделювання, керування та інформаційні технології, 2019)
The proposed computer model allows us to investigate the operation of the generator in normal and emergency modes, under dedicated load, or as part of a power system. The model allows to obtain graphs of instantaneous values ​​of currents, voltages, generator speed, active power.